The influence of surface nanoroughness, texture and chemistry of TiZr implant abutment on oral biofilm accumulation. Issue 6 (20th February 2014) - Xing, Rui; Lyngstadaas, Ståle P.; Ellingsen, Jan Eirik; Taxt‐Lamolle, Sébastien; Haugen, Håvard J.
Abstract: Objectives: The aim of the study was to examine surface nanoroughness, texture and chemistry of dental implant abutment and to investigate how these parameters influence oral biofilm formation in healthy subjects. Materials and methods: Eight different nanorough TiZr surfaces were produced by polishing, machining, cathodic polarization and acid etching. Surface topography was examined using field emission scanning electron microscope and a blue light laser profilometer. Surface chemistry was analyzed by secondary ion mass spectrometry and X‐ray photoelectron spectroscopy. Surface hydrophilicity was tested by measuring contact angle on the surfaces. A human in vivo study using a splint model was employed to evaluate oral biofilm accumulation on these surfaces. Results: Different surface textures (flat, grooved and irregular) were created with nanoroughness from 29 to 214 nm. Some test surfaces were incorporated with hydrogen by cathodic polarization and/or acid etching with HCl/H2 SO4 . Nanoroughness (Sa ) positively correlated with microbial adhesion. Biofilm accumulation was less pronounced on flat and grooved than on irregular surfaces. No significant association between hydrogen content or hydrophilicity of the surface and biofilm accumulation was observed. Conclusions: Nanoroughness (< 214 nm) and surface texture influence oral biofilm accumulation independent of surface chemistry and hydrophilicity. Surface hydrogen, which has previously been shown to promote fibroblast growth, does not affect biofilm formation.